Risk Management in Sharia Financing: Credit Risk Analysis in Murabahah Financing in Islamic Banking in Surabaya - Maruly, Salsa (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Understanding of risks and risk concepts related to Sharia financing is widely known in the financial industry using profit-and-loss sharing (PLS). However, the risk in a murabahah financing contract is the counterparty’s inability to complete its obligations within the agreed time period. Therefore, it is called credit risk or default risk. Credit risk occurs when customers fail to make payments on time after the bank completes the transfer of assets. Therefore, this has an impact on bank growth because the banking business is not well-positioned to cover these risks. Therefore, the bank may impose a penalty on the outstanding balance. The aim of this research is to highlight the determinants of credit risk and issues surrounding Islamic banks in Surabaya in terms of Murabahah financing and how to manage them using appropriate techniques. Finally, explore the concept of credit risk management, which might be able to solve the problems that arise. The research results found that credit risk can be managed well by increasing the use of a comprehensive business partner reference checklist regarding their character and past performance as well as their comprehensive database.